Małe i średnie przedsiębiorstwa a wzrost gospodarczy - Prędkiewicz, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Small and medium firms are assumed to be an important factor of economic growth. In this paper, the author tries to find theoretical, empirical and practical arguments which can confirm positive or negative correlation between entrepreneurial activity of SME and economic growth. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 397-407